Novel insight into the regulation of steroid hormone receptor signaling by protein arginine methyltransferase 6 and regulation of TRIM22 expression in breast cancer - Sun, Yang (2013)
Estrogen and progesterone are critically involved in the development of breast cancer and their effects are mediated by the estrogen receptor (ER) and progesterone receptor (PR) respectively. The activities of ER and PR are regulated at multiple steps of steroid hormone receptor (SHR) signaling pathway. Post-translational modifications (PTMs) play pivotal roles in regulating SHR signaling, enable quick responses of these receptors to stimuli without the need for new protein synthesis. Initial mass spectrometry analysis of PTMs on ER identified multiple methylated arginines, suggesting that arginine methylation is an important player regulating ER activity. The objectives of the first part of the thesis were to identify protein arginine methyltransferases (PRMTs) that methylate ER and PR and to determine the functional relevance of the methylation. This study showed that PRMT6 binds to ER, PR and androgen receptor (AR), and methylates them independent of ligand. The site of the interaction and mode of regulation by PRMT6 seems to vary among the receptors but the role of PRMT6 in regulating ER activity has been further defined. PRMT6 binds to ER at the C-terminus domains (LBO-region F) and proximity ligation assays indicated that PRMT6 interacts with ER exclusively in the nucleus. PRMT6 overexpression enhances ER ligand-independent and ligand-induced activity via different mechanisms. PRMT6 significantly enhances the ligand-independent activity of ER without the need for its methyltransferase activity. We present evidences suggesting that the ligand-independent activation of ER by PRMT6 is mediated through its binding to ER which may lead to dissociation of chaperone heat shock protein 70 (Hsp70) and Hsp90. On the other hand, enhancement of ligang-induced ER activity requires enzymatically active PRMT6 and possible arginine residues targeted by PRMT6 have been identified. In light of the recent report that PRMT6 dysfunction is associated with worse prognosis in ER-positive breast cancers, our results suggest that PRMT6 may promote the mitogenic effect of ER both in the presence and absence of estrogen. The increase in ligand-independent ER signaling with high PRMT6 expression level may result in hormone-independent tumor growth which is resistant to the inhibitory effect of tamoxifen. In contrast to the mitogenic role of ER in breast cancer, PR can exert inhibitory effect on breast cancer growth. Progesterone-induced growth inhibition in PR-transfected MDAMB-231 cells was associated with a remarkable upregulation of tripartite motif-containing 22 (TRIM22), a p53 and interferon (lFN) target gene. The objective of the second part of the thesis work was to understand the regulation of TRIM22 gene expression and its clinical significance. TRIM22 protein level is consistently downregulated in breast cancer cell lines and breast tumor tissues as compared to non-malignant mammary epithelial cells and normal breast tissues, making it a potential marker for breast malignancy. TRIM22 expression also correlates with p53 expression in normal breast tissue and it can be induced upon p53 activation in non-malignant cell. However, in breast cancer cells, TRIM22 expression is not inducible in response to p53 activation by genotoxic drugs, suggesting that regulation of TRIM22 by p53 is specifically disrupted during tumorigenesis. In addition, TRIM22 is also a regulator of PR activity. It upregulates both the expression level and ligand induced activity of full length PR but inhibits ligandindependent activity of LBO truncation PRo Together with the reported growth inhibitory role of TRIM22 for leukemic cells, this study presents evidence that TRIM22 may inhibit the growth of breast cancer cells via p53 and PR signaling pathway. Further correlation of TRIM22 expression in clinical breast cancer samples with clinicopathological parameters will shed light on the prognostic value of TRIM22 in breast cancer.